2007
DOI: 10.1371/journal.pcbi.0030221
|View full text |Cite
|
Sign up to set email alerts
|

STDP in a Bistable Synapse Model Based on CaMKII and Associated Signaling Pathways

Abstract: The calcium/calmodulin-dependent protein kinase II (CaMKII) plays a key role in the induction of long-term postsynaptic modifications following calcium entry. Experiments suggest that these long-term synaptic changes are all-or-none switch-like events between discrete states. The biochemical network involving CaMKII and its regulating protein signaling cascade has been hypothesized to durably maintain the evoked synaptic state in the form of a bistable switch. However, it is still unclear whether experimental … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
193
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 141 publications
(206 citation statements)
references
References 123 publications
(197 reference statements)
12
193
1
Order By: Relevance
“…For example, the magnitude of weight change induced by different stimulation protocols in this model is generally smaller than that observed empirically, despite the fact that the relative frequency and conductance of potentiated and depressed synapses are matched to published data [36, 37, 44; see Methods]. Furthermore, specific AMPAr and NMDAr conductances are not affected by changes in putative synaptic weight which, although in line with many theoretical studies of plasticity induction, is clearly at odds with the situation in vivo [18,[42][43][44][45][46][47][48]. It has been demonstrated that changes in AMPAr conductance associated with the expression of long-term synaptic plasticity are accompanied by concomitant changes in NMDAr conductance [69,76].…”
Section: Discussionsupporting
confidence: 76%
See 4 more Smart Citations
“…For example, the magnitude of weight change induced by different stimulation protocols in this model is generally smaller than that observed empirically, despite the fact that the relative frequency and conductance of potentiated and depressed synapses are matched to published data [36, 37, 44; see Methods]. Furthermore, specific AMPAr and NMDAr conductances are not affected by changes in putative synaptic weight which, although in line with many theoretical studies of plasticity induction, is clearly at odds with the situation in vivo [18,[42][43][44][45][46][47][48]. It has been demonstrated that changes in AMPAr conductance associated with the expression of long-term synaptic plasticity are accompanied by concomitant changes in NMDAr conductance [69,76].…”
Section: Discussionsupporting
confidence: 76%
“…The slow time constant of Calcium influx through the NMDA receptor is also shorter than that measured experimentally, which has been shown to correspond well with the time course of deactivation following glutamate release [~150ms; 57]. However, that study measured the time course of Calcium influx following unitary NMDAr activation, whereas we are concerned with NMDAr kinetics when significant post-synaptic depolarisation follows glutamate binding by ~50-100ms, which may be significantly more complex [46].…”
Section: The Range Of Temporal Interactions Slow Time Constants and mentioning
confidence: 59%
See 3 more Smart Citations